Stability evaluation of three-layered journal bearing with slip/partial slip. Issue 3 (8th May 2017) - Rao, T.V.V.L.N.; Rani, A.M.A.; Awang, M.; Hashim, F.M.
Abstract : Purpose: This paper aims to present stability of a three-layered journal bearing considering magnitude of the layers' thicknesses and viscosities with slip/partial slip on the bearing surface. Design/methodology/approach: Modified Reynolds equation based on one-dimensional analysis is derived for a three-layered journal bearing with slip/partial slip. Dynamic coefficients are derived based on infinitesimal perturbation method. Linearized stability analysis is presented taking into account slip/partial slip on bearing surface; thicknesses and viscosities of bearing surface layer; and core layer and journal surface layer. Findings: Results of threshold speed and critical whirl frequency ratio coefficients ( C ω, C Ω ), stiffness ( Kij for i = x, y ) and damping ( Bij for i = x, y ) coefficients and threshold speed (ω s ) and critical whirl frequency ratio (Ω s ) are presented. The bearing surface is analyzed for slip (total surface with slip) and partial slip (partial surface with slip). The slip-on bearing surface reduces stability, while partial slip improves bearing stability. The threshold speed coefficient ( C ω ) decreases with slip on bearing surface. The threshold speed (ω s ) and critical whirl frequency ratio (Ω s ) are influenced by the variation of threshold speed coefficient ( C ω ) and critical whirl frequency ratio coefficient ( C Ω ), respectively. A three-layered journal bearing with partial slip and thick high viscosity bearing surface layer results in higher threshold speed coefficient and has a potential to improve stability of journal bearing. The analyses indicate that optimal angular extent of partial slip region (θs ) enhances the stability of journal bearing. Originality/value: The paper presents parametric study of stability coefficients ( C ω and C Ω ) and evaluation of threshold speed (ω s ) and critical whirl frequency ratio (Ω s ) of a three-layered journal bearing with slip/partial slip.